Search for FCNC single top-quark production at √s = 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
A search for the production of single top-quarks via flavour-changing neutral-currents is presented. Data collected with the ATLAS detector at a centre-of-mass energy of √s = 7 TeV, corresponding to an integrated luminosity of 2.05 fb-1, are used. Candidate events with a semileptonic top-quark decay signature are classified as signal- or background-like events by using several kinematic variables as input to a neural network. No signal is observed in the neural network output distribution and a Bayesian upper limit is placed on the production cross-section. The observed upper limit at 95% confidence level on the cross-section multiplied by the t → Wb branching fraction is measured to be σqg→t × B(t → Wb) < 3.9 pb. This upper limit is converted using a model-independent approach into upper limits on the coupling strengths κugt/Λ < 6.9 · 10-3 TeV-1 and κcgt/Λ < 1.6 · 10-2 TeV-1,where Λ is the new physics scale, and on the branching fractions B(t → ug) < 5.7 · 10-5 and B(t → cg) < 2.7 · 10-4.